Teak (Tectona grandis Linn. f) and Edaphic Factors Affecting the Regeneration of Woody Species and Their Functional Traits in Economic Forest Plantation, Northern Thailand - Lamthai Asanok; Rungrawee Taweesuk; Torlarp Kamyo (International Journal of Forestry Research)
Improved understanding of relationships among plant traits, stand characteristics, and soil properties can provide insights into the regenerating tree communities of commercial teak plantations. We investigated whether plant traits could be used to predict the natural regeneration of woody species in teak plantations with different soil and stand conditions. Data were collected in fifty 20 m × 20 m plots that were established in teak plantations of varying ages in northern Thailand. We analyzed differences in stand characteristics, soil properties, and community-level functional traits among sites. The RLQ analysis was performed to explore the associations among species abundances, plant traits, and a combined set of soil variables and stand characteristics. Our results showed that tree species with high leaf dry matter contents and high wood density dominated communities in an older teak plantation and were associated with high OM and N concentrations. Trees with larger leaves are increased in plantations that had experienced their first teak thinning, and were rich in organic matter. Species with high specific leaf areas increased in sites with high teak basal areas and which had experienced more intense thinning on fertile soils. Thick-leaved species had high importance values on sites with high densities of teak and infertile soils. Our results indicated that tree communities with similar conspecific traits were associated with specific soil and stand conditions in teak plantations. A knowledge of these regeneration dynamics may allow forest managers to encourage increased natural regeneration and enhanced diversity in commercial teak plantations.